(untitled) (Journal of NELTA, 2010)
The objective of this paper is to explore one of the aspects of the problem of the use of information communication technologies in English as a Second Language teaching and learning. There has been studies on the effectiveness of computer dictionaries and encyclopedias in teaching and learning English language as well as the attitude of school English teachers to the application of computerbased inquiry software that are considered to be new in Kazakhstani comprehensive education. This article argues that computer dictionaries and encyclopedias contribute to development of English language learning by providing a teacher and a learner with a didactic tool for free access to a variety of materials, comfortable information search opportunities, and communication as well. The study that was conducted in Karaganda city high school, Kazakhstan, shows that the computer dictionaries and encyclopedias motivate school students to learn English language more enthusiastically. Key words: computer-based inquiry software, hypermedia, language skills, experimental teaching DOI: 10.3126/nelta.v14i1.3091 Journal of NELTA Vol.14, No 1&2, 2009 December Page: 55-62